Structural Identification of Masonry Residential Buildings Considering Wall Openings - Toydemir, Burak; Kocak, Ali (BUDAPEST UNIV TECHNOLOGY ECONOMICS, 2020)
Although one-story residential masonry structures are thought not to be vulnerable to seismic actions, many heavily damaged and/or collapsed instances of these types of structures have been observed in the past strong earthquake events. Hence, the evaluation of their safety requires much attention in terms of more precise numerical models. In-situ vibration tests together with laboratory tests on masonry specimens provide valuable information for structural parameter identification that can be used to develop accurate numerical models. These numerical models then can be used for evaluation of the response and seismic safety. While many specific methods and parameters can be adopted in numerical modeling, linear material properties of a structure are expedient in response analysis. Hence, an equation to be used to determine the homogenized linear model parameters for masonry walls with openings is proposed in this study. The equation has been developed based on the percentage of the openings on the wall. The effect of wall openings on the stiffness and the total strength of one-story masonry structures have been evaluated by using the experimental data and the calibrated finite element models. In-situ ambient vibration and material tests have been conducted on three masonry buildings with identical materials and the results from these experiments were used to verify the accuracy of the formulation.
Keywords: masonry; wall openings; Operational Modal Analysis; structural identification; time history analysis; DYNAMIC IDENTIFICATION; INTERFACE MODEL; MODAL IDENTIFICATION; DAMAGE ANALYSIS; BRICK-MASONRY; FRICTION; SURFACE; Engineering